2016
DOI: 10.1371/journal.pone.0159015
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Staff Wellbeing, Burnout, and Patient Safety: A Systematic Review

Abstract: ObjectiveTo determine whether there is an association between healthcare professionals’ wellbeing and burnout, with patient safety.DesignSystematic research review.Data SourcesPsychInfo (1806 to July 2015), Medline (1946 to July 2015), Embase (1947 to July 2015) and Scopus (1823 to July 2015) were searched, along with reference lists of eligible articles.Eligibility Criteria for Selecting StudiesQuantitative, empirical studies that included i) either a measure of wellbeing or burnout, and ii) patient safety, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
951
3
24

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 1,161 publications
(1,077 citation statements)
references
References 56 publications
32
951
3
24
Order By: Relevance
“…Indeed, more broadly, a recent review in healthcare staff demonstrated that burnout and poor wellbeing were associated with poorer patient safety [65].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, more broadly, a recent review in healthcare staff demonstrated that burnout and poor wellbeing were associated with poorer patient safety [65].…”
Section: Discussionmentioning
confidence: 99%
“…Burnout has been linked to increased absenteeism, the abandonment of jobs, a reduction in health care quality, an increase in errors, and a reduced level of patient safety [52][53][54] ; thus, identifying and treating professionals with burnout are important. In addition, the presence of high burnout prevalence rates has been associated with poor quality of nursing care, increased number of patient falls, medication errors, and increased incidence of infections 55 -factors that adversely affect patient care.…”
Section: Version Of Mbimentioning
confidence: 99%
“…To develop interventions to reduce errors, a growing body of research has sought to understand underlying causes and contributing factors. One area has focused on the role that human factors such as staff burnout and depressive symptoms may play (Hall et al, 2016).…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…When it occurs, burnout may have wide-ranging consequences such as lower staff empathy and poorer patient experience (Vahey et al, 2004, Leiter et al, 1998, Passalacqua and Segrin, 2012. Several studies indicate that burnout may also be linked with clinical errors (Hall et al, 2016), although the majority of this research has been amongst doctors.…”
Section: Introduction Backgroundmentioning
confidence: 99%